Scanning photocurrent microscopy of 3D printed light trapping structures in dye-sensitized solar cells - Knott, Andrew N.; Makarovsky, Oleg; O’Shea, Paul; Tuck, Christopher; Wu, Yupeng (Elsevier, 2018)
Converting solar energy directly into electricity as a clean and renewable energy resource is immensely important to solving the energy crisis and environmental pollution problems induced by the consumption of fossil fuels. Dye-sensitized solar cells (DSSCs) provide a technically and economically credible alternative that could challenge the dominance of conventional p-n junction photovoltaic devices in the solar energy market. DSSCs use dye molecules adsorbed at the surface of nanocrystalline oxide semiconductors such as TiO2 to collect sunlight. These thin films require a large surface area, to adsorb many dye molecules, and mesoporous channels so the electrolyte can permeate the film and regenerate the dye molecules. This favourable morphology is traditionally achieved by the random assembly of a network of nanoparticles by the sintering process. Two-photon polymerization is a 3D printing technique used to fabricate structures with feature resolutions down to 100 nm. We use this technique to fabricate TiO¬2 thin films of optimised 3D micro-design for use in DSSCs. Our films have a considerable advantage over the conventional (random assembly) films as it allows the implementation of light scattering designs which are shown to significantly enhance photocurrent in the cell by up to ~25%.